2011
DOI: 10.5146/tjpath.2010.01046
|View full text |Cite
|
Sign up to set email alerts
|

Lsil/asc-h (lsil-h) in cervicovaginal smear: histopathological outcomes and clinical significance

Abstract: Objective: The aim of the study was to investigate the importance of consumption of the epidermis as an additional diagnostic criteria for malignant melanoma and to evaluate its relationship to clinicopathological findings. Material and Method:The age, gender, localization of the lesion and the histopathological parameters such as tumor type, Breslow thickness, ulceration, Clark's level, mitosis/mm 2 , lymphocytic infiltration were noted in 40 malignant melanoma cases. Consumption of the epidermis was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Our results regarding the biopsy outcomes of LSIL‐H are similar to others: the rate of discovery of high grade dysplasia is higher than for unqualified LSIL and about the same as for ASC‐H . These findings have been recently reviewed elsewhere and are consistent across studies, supporting the robustness of the LSIL‐H category.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results regarding the biopsy outcomes of LSIL‐H are similar to others: the rate of discovery of high grade dysplasia is higher than for unqualified LSIL and about the same as for ASC‐H . These findings have been recently reviewed elsewhere and are consistent across studies, supporting the robustness of the LSIL‐H category.…”
Section: Discussionsupporting
confidence: 89%
“…The interpretive category most commonly known as “low grade squamous intraepithelial lesion, cannot exclude high grade squamous intraepithelial lesion” (LSIL‐H), though not recognized by the 2001 Bethesda System, has been extensively studied and used. The Bethesda authors briefly refer to the category as “squamous intraepithelial lesions of indeterminate grade.” Other authors refer to this category as a combination of the Bethesda classifications of “low grade squamous intraepithelial lesion” (LSIL) and “atypical squamous cells, cannot rule out high grade squamous intraepithelial lesion” (ASC‐H) . Regardless of terms, as a practical matter, there seems to be agreement that this category consists of cases with definite low grade dysplastic changes in combination with rare or obscured cells concerning for, but not diagnostic of, high grade squamous intraepithelial lesion (HSIL).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LSIL‐H is a cytologic interpretation that is equivocal for HSIL and is now recognized to harbor an intermediate risk of CIN2+ compared with LSIL and HSIL . Our study of more than 350,000 PTs including more than 17,000 abnormal tests demonstrates that the frequency of LSIL‐H interpretations increased at our institution over a 6‐year period with a simultaneous decrease in HSIL interpretations.…”
Section: Discussionmentioning
confidence: 71%
“…LSIL‐H refers to smears fulfilling criteria for both LSIL and atypical squamous cells, cannot exclude HSIL (ASC‐H) or smears with squamous intraepithelial lesions (SIL) of indeterminate grade. Various studies investigating LSIL‐H relative to the other TBS diagnostic categories have consistently found an intermediate risk of histologic follow‐up of cervical intraepithelial neoplasia 2 or greater (CIN2+) relative to LSIL and HSIL and significantly greater prevalence of high‐risk HPV (hrHPV) relative to ASC‐H . For these reasons several investigators have concluded that LSIL‐H warrants a distinct diagnostic category in cervical cytology reporting.…”
mentioning
confidence: 99%